Soil Development from Volcanic Ash Based on Different Pyroclastic Composition - Ahmad, Asmita; Solle, Muchtar Salam; Lopulisa, Christianto (UNIVERSITY OF LAMPUNG, 2019)
Potential volcano in several provinces in Indonesia played a significant role in the formation and quality of soil development. Soils that developed from the volcanic ashes often thought to contribute greatly to improve soil fertility, without regard to the nature and composition of the volcanic ash produced. Volcanic ash generated from the results in volcanic activity has a different composition, there are basaltic, andesitic and granitic, thereby affecting the process of formation and characteristics of the soil. The Objective of this study is to determine the soil development from different types of pyroclastic generated from Lokon volcano in North Sulawesi. The coordinates of research was in 1o 21' 18.0